2018
DOI: 10.1167/tvst.7.5.20
|View full text |Cite|
|
Sign up to set email alerts
|

Variability of Foveal Avascular Zone Metrics Derived From Optical Coherence Tomography Angiography Images

Abstract: PurposeTo characterize sources of inter- and intrasubject variability in quantitative foveal avascular zone (FAZ) metrics.MethodsTwo 3×3-mm optical coherence tomography angiography scans (centered on the fovea) were acquired in both eyes of 175 subjects. An image of the superficial plexus was extracted from each scan and segmented twice by a single observer. Four quantitative FAZ morphology metrics (area, axis ratio, acircularity, major horizontal axis angle) were calculated, and a variance components analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 62 publications
1
41
0
3
Order By: Relevance
“…However, considering the retrospective nature of this study, our results should be treated with caution, and future prospective cohort studies are needed to confirm this finding. Previous studies indicated that FAZ [7] is altered in some vascular-related diseases, such as like diabetic retinopathy [8,9] and retinal vein occlusion (RVO) [10]. FAZ is also correlated with visual acuity in RVO [3] and diabetic retinopathy without diabetic macular edema [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the retrospective nature of this study, our results should be treated with caution, and future prospective cohort studies are needed to confirm this finding. Previous studies indicated that FAZ [7] is altered in some vascular-related diseases, such as like diabetic retinopathy [8,9] and retinal vein occlusion (RVO) [10]. FAZ is also correlated with visual acuity in RVO [3] and diabetic retinopathy without diabetic macular edema [9].…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate whether the FAZ morphometry observed in our patients with ACHM differed from normal, we compared their data to a group of 175 previously published patients with no vision pathology. 50 The mean ± SD FAZ area for the control group was 0.280 ± 0.101 mm 2 , which was not significantly different from the patients with ACHM (0.281 ± 0.112 mm 2 ; P = 0.94, Mann-Whitney U test). In contrast, the circularity index of the FAZ in the control group (mean ± SD = 0.682 ± 0.106) was significantly greater than that for the patients with ACHM (0.501 ± 0.093; P < 0.0001, unpaired t-test).…”
Section: Resultsmentioning
confidence: 70%
“…FAZ evaluation needs cautiousness because of the greater variations among subjects and OCTA limitations. 36,37 We speculated that the FAZ area enlargement was the process of FAZ area increase toward the normal values compared to the FAZ area of the fellow eyes. Despite that, there were still controversies regarding whether the fellow eye could be considered a control for FAZ studies.…”
Section: Discussionmentioning
confidence: 99%